Clinical features and therapeutic responses of idiopathic orbital myositis. Issue 2 (3rd December 2014) - Ota, Makiko; Shimizu, Toshio; Yoshida, Hiroshi; Kawata, Akihiro; Kinoshita, Masako; Nakano, Satoshi; Isozaki, Eiji; Matsubara, Shiro
Abstract: Background: Orbital myositis is a rare and relatively rapid‐onset disease, resulting in inflammation mainly of the single or multiple extraocular muscles, for which the optimal treatment has not yet been fully established. Aim: To evaluate clinical features, therapeutic responses and prognostic factors of idiopathic orbital myositis. Methods: In five patients diagnosed with idiopathic orbital myositis (age of the disease onset 20–81 years), the clinical features, laboratory and radiographic findings, therapeutic response, and prognosis were analyzed retrospectively. Results: All patients showed restriction of ocular movements or orbital pain aggravated by the movements, and one of them showed a visual disturbance caused by the optic nerve compression. Their magnetic resonance imaging showed a thickening of the orbital eye muscles. Two patients who started steroid hormone therapy within 1 month from the disease onset (starting dose: more than prednisolone 50 mg/day) showed quick recovery; both of them had a relapse and they improved again by steroid therapy. Another patient who was started with prednisolone 30 mg/day at the 34th day showed slight residual limitation of ocular movement. However, in the other two patients who received steroid therapy later than 6 months (starting dose: methylprednisolone 1000 mg/day or prednisolone 30 mg/day), the symptoms were intractable, and one of them underwent surgical treatment. Conclusion: Early initiation of appropriate immunotherapy using a sufficient amount of steroid hormone is essential to improve the prognosis of idiopathic orbital myositis.